“Ehhh! Cabeça de Cuia!!!”: memória e cidade na obra musical de Teófilo Lima (1994-2018) - Silva de Moura, Gustavo (Temporalidades, 2020)
This article aims to analyze the relationship between music, memory, Piauí culture and Parnaíba City, localized in Piauí coast, taking as kaleidoscope a phonographic production of the singer and composer Teófilo Lima and his trajectory. Will be analysis the biography of the musician, important point in understanding the references brought in his songs. In his work is latent Piauí culture and collective memory about Parnaíba City, shaping his compositions with the rock that is taken to the public, showing his daily perception of culture and society. Because of its insertions in the great marks in the history of rock and pop music of Piauí, analyzing its musical trajectory makes it possible to focus on the relations between global and local present in the urban music of Piauí and what its movements and references that allowed musical authenticity.